2013
DOI: 10.1016/j.sleep.2012.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Napping in English preschool children and the association with parents’ attitudes

Abstract: . (2013) 'Napping in English preschool children and the association with parents' attitudes.', Sleep medicine., 14 (4). pp. 352-358. Further information on publisher's website:http://dx.doi.org/10.1016/j. sleep.2012.12.010 Publisher's copyright statement: NOTICE: this is the author's version of a work that was accepted for publication in Sleep medicine. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 22 publications
1
22
1
1
Order By: Relevance
“…The sedentary nature of television watching may therefore encourage napping even if it is not needed. Indeed, Jones and Ball (2013) found that a majority of three-year-olds in their sample engaged in opportunistic napping, such as falling asleep in the living room while watching television. The exact role that media plays in napping should be explored in future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sedentary nature of television watching may therefore encourage napping even if it is not needed. Indeed, Jones and Ball (2013) found that a majority of three-year-olds in their sample engaged in opportunistic napping, such as falling asleep in the living room while watching television. The exact role that media plays in napping should be explored in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Although napping patterns evolve with age, suggesting a biological explanation for their extinction, other factors also influence napping, such as daycare attendance and parental attitudes (Jones & Ball, 2013;Wiggs, 2015). In this way, napping behaviors may reflect schedules and preferences of adults rather than children.…”
mentioning
confidence: 99%
“…Napping, and especially nap duration, seem to be predominantly influenced by the environment (shared sleeping environment, socio-economic, familial, and educational influences, and sleep hygiene), with a lesser effect from genetic factors and without gender differences. [33][34][35][36] Cultural influences appear to be weaker than environmental ones, at least in countries. 37 A majority of the children in the Asian countries took naps but had later bedtimes and shorter night-time sleep compared to the Caucasian children, resulting in no differences in 24-hour TST between the two cultures.…”
Section: Toddlers and Childrenmentioning
confidence: 99%
“…A C C E P T E D ACCEPTED MANUSCRIPT 34 Zaregarizi et al 97 reported an acute reduction in blood pressure (systolic and diastolic blood pressure) and heart rate. The authors also reported that this reduced blood pressure and heart rate could not be attributed solely to the supine position, because the measurements taken during the nap were significantly lower than the levels observed when the subjects were lying supine in relaxed wakefulness.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Students could be instructed to request a nap whenever feeling too drowsy to learn more. This would allow them to prepare for memory acquisition following a bad night of sleep, and to self-regulate the offline consolidation of relevant memories soon after learning, as has been suggested for preschool children [36]. However, allowing students to nap upon request bears several risks.…”
Section: From Laboratory To Classroommentioning
confidence: 99%